The Gender-Based Violence and Precarity Nexus: Asylum-Seeking Women in the Eastern Mediterranean - Tastsoglou, Evangelia; Petrinioti, Xanthi; Karagiannopoulou, Chara (Frontiers in Human Dynamics, 2021)
This paper derives from a larger research on gender-based violence and precarity in the forced migration journeys of asylum-seeking women transiting through the Eastern Mediterranean route and arriving in Greece, in the tumultuous, second decade of the 21st century. In this paper we present the findings from the first phase of the research. We analyze and discuss the opinions and information gathered through semi-structured interviews with twenty key informants: service providers, staff of international and national NGOs, local government staff and public officials. Our findings locate the five points / loci in irregular cross-border movements and arrival at an EU member-state where precarity interweaves with gender-based violence. The first locus, is in transit and EU and Greek border crossing; second, during the asylum determination process; third, in their everyday life when they must deal with homelessness and harsh living conditions; fourth, in the deficiency of care services further aggravated by intersectional discrimination; finally, by being trapped in abusive settings and relationships due to the ineffective state response, a sluggish criminal justice system, and the victim’s financial dependence on the perpetrator. Adopting a feminist and intersectional approach our analysis shows that violence and precarity are co-constituted and reinforce each other through the undermining of the citizenship status of asylum seekers and the inscription, on their bodies and lives, of unequal gendered social and institutional power relations.